Development of 3D Augmented Reality Based Learning Media as an Effort to Improve the Quality of Literacy in High Schools - Rassyi, Sultan Fakhrur; Isro'ullaili, Isro'ullaili (Indonesian Journal Publisher, 2024)
The development of globalization requires countries to develop technology in various aspects of life. Quality education is one of the highlights, because it is the key to solving various ongoing problems, including students' low interest in literacy, especially digital literacy. This research aims to produce solutions for learning Indonesian at the high school level through the application of Augmented Reality (AR) technology developed by Gratise. Inc. The application of AR in Indonesian language learning is considered minimal and relevant, especially in increasing interest and quality of learning. The concept of this application will focus on providing language detectors, Indonesian folklore, and expert information in the language domain. The objectives of developing this application are: (1) Make it easier for students to utilize technology in learning, (2) Improve the quality of educational devices, and (3) Improve the quality of student exam results in learning Indonesian in high school. Through the development of 3D AR-based learning media, it is hoped that it can make a significant contribution to increasing student literacy in high school.